Using Autoclave Furnace to Improve Properties of Mixing an Autoclaved Aerated Concrete Waste with Window Glass Waste (Journal of University of Babylon for Engineering Sciences, 2018)
Autoclaved aerated concrete (ACC) or thermostone is now becoming increasingly used in constructions, building and partition works due to its  properties such as a highly thermal insulating concrete-based material used for both internal and external construction, light weight and large size. However,  its low compressive strength and high porosity affected its use.In this research the experimental part focused on mixing an autoclaved aerated concrete (AAC) in the form of powder with different ratios of window glass wastes powder, then study the influence of these additives onto properties of thermostone in  terms of physical (absorption, porosity, density), mechanical (compressive and hardness), and thermal properties (thermal conductivity and thermal shock). The bulk density increased to about (1562Kg/m3), porosity and water absorption have been decreased to about (39.8 %, , 23.44%) respectively with the addition ratio (30) %  by weight. of glass. Also the compressive strength has been getting good result (26.27 N/mm2) and hardness, improved (13.88) at the percentage of waste glass (30) % by weight compared to the sample with no-additive. Finally, thermal conductivity with the result (0.5311 watt/m.◦c) at the same percentage of waste glass, while thermal shock showed well result with the additives (10, 20, 30) % by weight at temperature 250 ◦C for 1 h, but failed at temperature of 350 ◦C for the same time.